Fixing the Fixings What Road to a More Representative Money Market Benchmark? - Brousseau, V. (IMF Working Papers, 2013)
Interest rate derivatives on major currencies, with notional outstanding amounts adding up to hundreds of trillions, are mostly indexed on Libor and Euribor benchmarks, as are hundreds of billions in loans to enterprises, mortgages and other retail loans to the real economy. Yet, the prevailing role of these benchmarks appears to be more a legacy from history rather than reflecting today?s structure of banks? funding. Building on earlier work (Brousseau, Chailloux, Durré, 2009), this paper discusses various options to move towards a new benchmarking system in the money market. It proposes a more ambitious benchmark design that would consist of a trade-weighted index that would systematically pool all short-term wholesale funding operations of banks per tenor